Decoding of the coupling between the brain and facial muscle reactions in auditory stimulation - Soundirarajan, Mirra; Kuca, Kamil; Krejcar, Ondrej; Namazi, Hamidreza (Technology anad health care, 2022)
BACKGROUND: Analysis of the reactions of different organs to external stimuli is an important area of research in physiological science. OBJECTIVE: In this paper, we investigated the correlation between the brain and facial muscle activities by information-based analysis of electroencephalogram (EEG) signals and electromyogram (EMG) signals using Shannon entropy. METHOD: The EEG and EMG signals of thirteen subjects were recorded during rest and auditory stimulations using relaxing, pop, and rock music. Accordingly, we calculated the Shannon entropy of these signals. RESULTS: The results showed that rock music has a greater effect on the information of EEG and EMG signals than pop music, which itself has a greater effect than relaxing music. Furthermore, a strong correlation (r= 0.9980) was found between the variations of the information of EEG and EMG signals. CONCLUSION: The activities of the facial muscle and brain are correlated in different conditions. This technique can be utilized to investigate the correlation between the activities of different organs versus brain activity in different situations.
Keywords: akustická stimulace; Electromyography; mozek; lidé; obličejové svaly; Facial Muscles; elektroencefalografie; Brain; Acoustic Stimulation; elektromyografie; Electroencephalography; Humans